Penggunaan Teknik Menulis Paralel dengan Latar Musik Klasik dalam Pengajaran Menulis pada Mahasiswa Jurusan Bahasa Inggris Fakultas Sastra Universitas Muslim Indonesia: Using Parallel Writing Technique with Classical Music Background in Teaching Writing to the Students of English Department Faculty of Letters Moslem University of Indonesia - Nirwana Darwis (Fenomena, 2017)
Writing in a foreign language remains a persistently difficult skill for many university students, often hindered by low productivity and lack of engagement. This study investigates the effectiveness of a parallel writing technique accompanied by classical music background in teaching writing to second-semester English department students. A quasi-experimental method was employed, involving an experimental group taught with classical music and a control group taught without music, both using parallel writing. Data were collected through pre-test and post-test writing assessments and a Likert-scale questionnaire measuring student interest. The findings revealed that the post-test scores of the experimental group were significantly higher than their pre-test scores, indicating that the combination of parallel writing and classical music substantially improved students' writing productivity. Furthermore, questionnaire results showed a mean interest score of 69.95 (interest category) for the experimental group, compared to 39.25 (uninterested category) for the control group. A significant positive correlation (Pearson correlation .474) was found between writing productivity and student interest when classical music was used. It is concluded that parallel writing with classical music background not only enhances writing productivity but also fosters greater student engagement. It is recommended that English teachers integrate this technique into their writing instruction to create a more relaxed and stimulating learning environment. Menulis dalam bahasa asing masih menjadi keterampilan yang sulit bagi banyak mahasiswa, seringkali terhambat oleh produktivitas rendah dan kurangnya keterlibatan. Penelitian ini menyelidiki efektivitas teknik menulis paralel dengan latar musik klasik dalam pengajaran menulis pada mahasiswa semester dua Jurusan Bahasa Inggris. Metode kuasi-eksperimen digunakan, melibatkan kelompok eksperimen yang diajar dengan musik klasik dan kelompok kontrol tanpa musik, keduanya menggunakan menulis paralel. Data dikumpulkan melalui pre-test dan post-test menulis serta kuesioner skala Likert untuk mengukur minat mahasiswa. Temuan menunjukkan bahwa skor post-test kelompok eksperimen secara signifikan lebih tinggi daripada pre-test, yang berarti kombinasi menulis paralel dan musik klasik secara substansial meningkatkan produktivitas menulis mahasiswa. Selain itu, hasil kuesioner menunjukkan skor rata-rata minat 69,95 (kategori tertarik) untuk kelompok eksperimen, dibandingkan 39,25 (kategori tidak tertarik) untuk kelompok kontrol. Terdapat korelasi positif yang signifikan (Pearson .474) antara produktivitas menulis dan minat mahasiswa ketika musik klasik digunakan. Disimpulkan bahwa menulis paralel dengan latar musik klasik tidak hanya meningkatkan produktivitas menulis tetapi juga menumbuhkan keterlibatan mahasiswa yang lebih besar. Direkomendasikan agar guru bahasa Inggris mengintegrasikan teknik ini dalam pengajaran menulis untuk menciptakan lingkungan belajar yang lebih rileks dan merangsang.